Strengthening Investment During the Covid-19 Pandemic Through Digital Technology for Millennials in Pekalongan City - Rohmah, Farida (ProBisnis : Jurnal Manajemen, 2023)
This study aims to describe and explain the existence of digital technology as a strengthening investment in the millennial generation during the Covid-19 pandemic in Pekalongan City. This research is a field research with a qualitative approach. Explorative to find further and deeper into other possibilities of the problem under study. The informants in this research are investment gallery assistants at the UIN K.H Abdurrahman Wahid Pekalongan campus and young investors (millennial generation) in Pekalongan City. The results of this study indicate that there is an interest of the millennial generation in stocks during the covid-19 pandemic because many millennial generation investors make stock transactions, with the expectation that stock prices will increase after the end of the pandemic. In addition, the role of digital technology has further increased investment during the co-19 pandemic in Pekalongan City. This indicates that it is important because of the growing digital technology, this will facilitate and increase investment during the Covid-19 pandemic by not violating health protocols and the lifestyle of people during the pandemic who are accustomed to work from home and online systems.